Catalysts for Transesterification of Vegetable Oils: A Review - C. U. Nwuche; R. U. Duru; O. Achugasim; O. J. Abayeh (Journal of Applied Sciences and Environmental Management)
The transesterification of vegetable oils is a critical process in the production of biodiesel, a renewable and biodegradable alternative to fossil fuels. This process involves the substitution of alcohols for ester groups in triglycerides, facilitated by catalysts that significantly influence reaction efficiency and biodiesel quality. This review examines the roles, mechanisms, and performance of homogeneous, heterogeneous, enzymatic, and nano catalysts in biodiesel production. Homogeneous catalysts, including acidic and alkaline variants, provide high reaction rates but pose challenges in product separation and environmental sustainability. Heterogeneous catalysts offer improved reusability and separation but are limited by higher costs and lower reaction rates. Enzymatic catalysts address free fatty acid and water-related issues, producing high-purity biodiesel with reduced environmental impact, while nano-catalysts enhance reaction efficiency through high surface area and catalytic activity. Challenges such as catalyst separation, contamination, and industrial scalability are explored alongside future directions, including the development of green and biomass-derived catalysts. This study underscores the need for innovative catalytic systems to advance biodiesel production's economic viability and environmental sustainability.